Sexual Harassment on Senior Highschool Female Students (Sains Humanika, 2021)
This research aims to determine sexual harassment on senior high school female students. The subjects of this research were 40 senior high school female students in Purwokerto, Banyumas, Central Java, as many as 40 people were selected using random sampling. Analysis of the data used is a descriptive analysis of the test categories through the help of SPSS 20.00 for windows. The results of the analysis show a range score of 109, a minimum score of 55, a maximum score of 164, a mean score of 98.37, a standard deviation score of 27.26 and a variant score of 743.112. Based on the results obtained from the data collection, the category of subjects of sexual harassment on senior high school female students in Purwokerto was very high at 1 subject or 2.5%, high at 10 subjects or 25%, medium at 18 subjects or 45%, low at 7 subjects or 17.5% and very low by 4 subjects or 10%.
Keywords: Sexual Harassment; Female Students.